Taxonomic monograph of Eugenia sect. Schizocalomyrtus (Myrtaceae: Myrteae), a group within Eugenia with unusual flowers - Giaretta, Augusto; Lucas, Eve; Sano, Paulo Takeo (Phytotaxa, 2021)
Taxonomic monograph of Eugenia sect. Schizocalomyrtus, supported by molecular and morphological evidence, is presented. The flowers of this section have unusual fused calyces that are contrasted with standard Eugenia flowers with free calyx lobes. Because the fused calyx recurs in Myrtaceae and has been historically misleading for taxonomists, a key to Neotropical genera with fused calyces is presented. Additionally, Eugenia sect. Schizocalomyrtus is circumscribed, and a key to the ten species included in this section (two newly described) is provided. Detailed species descriptions, distribution and habitat notes, phenology, conservation status, nomenclatural and taxonomic comments, illustrations and distribution maps are also provided.